The Effect Of Giving Beet Juice With Red Guava On Hemoglobin Levels In Anemic Pregnant Women - Sri Mulyani, Nunung; Oktarina , Adelia; Rachmawati, Rachmawati (Poltekkes Kemenkes Bengkulu, 2025)
Anemia in pregnant women can cause complications for both the mother and fetus. One non-pharmacological way to increase hemoglobin levels is by consuming iron-rich and vitamin C-rich foods, such as beetroot and red guava. This study combines beetroot juice with red guava because the vitamin C in red guava enhances iron absorption from beetroot, thereby increasing hemoglobin levels. This study aims to determine the effect of beetroot juice with red guava on hemoglobin levels in anemic pregnant women in the working area of Piyeung Public Health Center, Montasik District, Aceh Besar Regency. This research used a quasi-experimental design with a two-group pretest-posttest approach. The sample consisted of 20 respondents, with 10 in the treatment group receiving beetroot juice with red guava and 10 in the control group receiving only water. The intervention lasted for 7 days. The findings showed that in the treatment group, hemoglobin levels increased from 9.320 g/dl to 9.990 g/dl, with a difference of 0.67 g/dl. In the control group, hemoglobin levels increased from 9.810 g/dl to 10.130 g/dl, with a difference of 0.32 g/dl, so it can be concluded that giving beetroot juice with red guava proven effective in increasing hemoglobin levels in pregnant women with anemia, with a p-value of 0,025 (p<0,05). Keyword : Anemia, Pregnant Women, Beetroot, Red Guava, Hemoglobin Levels.